2016
DOI: 10.1016/j.parepi.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma radiation on life history traits of Aedes aegypti (L.)

Abstract: Aedes aegypti is an important vector for Dengue and Dengue hemorrhagic fever. Considering its medical importance and its relevance as a model system, this study was undertaken to evaluate the impact of different doses of gamma radiation for three generations of A. aegypti. Two to three days old virgin males of A. aegypti were irradiated with 15 doses of gamma radiation, ranging from 1 to 50 Gy and were immediately mass mated with the same aged virgin females. Observations were made for changes on their life hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Indeed, in other studies, Ae . aegypti females that mated with sterile males continued to lay eggs even when males have been exposed to doses in the range 10 to 300 Gy [39, 40]. Similarly, An .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in other studies, Ae . aegypti females that mated with sterile males continued to lay eggs even when males have been exposed to doses in the range 10 to 300 Gy [39, 40]. Similarly, An .…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be possible to retain partial fitness if there is also selection for certain life history traits during inbreeding [80]. We show that laboratory populations maintained at low census sizes (N = 100) also experience inbreeding depression, and the loss of fitness correlates strongly with decreased effective population size.…”
Section: Discussionmentioning
confidence: 84%
“…aegypti mosquitoes ranges from 60-80 Gy. Shetty et al (2016) reported the effect of gamma irradiation on doses of 0-50 Gy on fertility, egg hatching, appearance and age of Ae. aegypti mosquitoes.…”
Section: Discussionmentioning
confidence: 99%